CHLAMYDIA PNEUMONIAE AS A FACTOR OF CORONARY HEART DISEASE DESTABILIZATION - Z. G. Gadjiyeva; A. S. Khasayev (Российский кардиологический журнал, 2003)
The aim of our study was to determine seroepidemiological links of Сhlamydia pneumoniae (CP), by IgA and IgG antibodies titers, with Coronary Heart Disease (CHD) in Makhachkala. A total of 122 coronary patients (average age of 54,6 ± 0,72 years) has been assessed (mean age of 54, 60, 72 years). The control group was made of 40 subjects (mean age 43,8 ± 1,28 years). Antibodies detection was made by means of solid phase immune enzyme assay. CP prevalence value in coronary patients has been found to have almost no difference from the one detected in the control group (p > 0,05). At the same time the difference in anti=CP=IgA in patients and healthy subjects was almost fourfold: 74,5% and 20,0 %, respectively (р < 0,001). A reliable difference in CP prevalence between groups of patients with stable and unstable angina was observed in IgA (p < 0,02) and in IgG (p < 0,05) as well. The data show previous CP infection and bacteria hosting not to be connected to CHD prevalence values. Only acute CP infection was associated with clinically manifest CHD.